Apakah Kualitas Antar Muka Berpengaruh pada Niat Penggunaan Terus (Use Continuance Intention) Aplikasi Gojek? Sebuah Studi pada Kalangan Generasi Z - Austion, Irwin; Simamora, Bilson (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
Generation Z is known for being critical and highly sensitive to prices, promotions, and technology. It is interesting to investigate how they use an application continuously. The authors postulate that the application's user interface quality is the key. Therefore, this research aims to investigate the influence of user interface quality on use continuation intention among Generation Z. To answer this research problem, the authors collected data using online questionnaires via Google Forms from 170 respondents selected through judgmental sampling. Data are analyzed using Structural Equation Modelling (SEM) with the help of WarpPLS 8.0. This study reveals that simplicity, directionality, informativeness, user-friendliness, comprehensiveness, personalization, and internal factors have a positive and significant effect on use continuation intention, while connectivity, interactivity, and continuity have no effect.